Kepemimpinan perempuan dan pilkada serentak - Saputra, Inggar; Asih, Nisa Wening (ARISTO, 2017)
Women who run in local elections (constituencies) are still considered minimal. This condition is very apprehensive because the constitution has mandated the quota of 30 percent of women who must be filled political parties. But the quota has not been met due to the lack of political participation of women in the struggle for power in politics. Participation is low due to gender discrimination that shaped the social and psychological environment of women itself, thus narrowing women's political opportunities. Therefore, political parties are expected to seriously encourage the participation and political education of women.